Octenidine dihydrochloride (oct): applications in dentistry- A review - DR. KETHIREDDY AKHILA; DR. SVSG NIRMALA (International Journal of Pharma and Bio Sciences, 2018)
Antiseptics and disinfectants are used comprehensively in hospitals and in various healthcare fields for a variety of topical and hard-surface applications. In the past decade, the use of antibiotics is restricted due to the spread of antimicrobial resistance. Now a days, there is an increased use of topical antiseptics, as these are less likely to induce resistance. The increased use of these topical antiseptics is attributed to the presence of multiple target sites, an unspecific mode of action and usage in higher concentrations. Wide use of antiseptics belongs to class of Guanidines. One such antiseptic that belongs to this class is Octenidine Hydrochloride (OCT). It differs from other Guanidines as the amide and ester structures are not part of the molecule. Therefore, the toxicologically critical part of the chlorhexidine molecule, 4-chloraniline, cannot be liberated, hence can be used safely. Octenidine was introduced in 1990 as a mucous membrane antiseptic. It has a broad antimicrobial spectrum and is effective against biofilm-forming organisms including MRSA, plaque-forming bacteria such as Actinomyces and Streptococcus spp, Chlamydia, Mycoplasma. It readily binds to negatively charged surfaces and can be used either prophylactically or therapeutically on the skin, mucosa and wounds. It is used widely in the medical field as antiseptic in areas of skin, mucous membrane, sterilization of IV catheters and wound disinfectant etc. In dentistry it is used as mouthwash, gutta-percha disinfectant, for biofilm inhibition on restorative materials, as a root canal medicament and root canal irrigant. Even though it has wide applications as per the literature, the knowledge of OCT is still a lacunae in dentistry. The objective of this paper is to discuss the Octenidine hydrochloride applications, the current evidence of its use and future recommendations in dentistry.